Historography of Science and Religion - Kwaśniewski, Jacek (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
The article shows the evolution of historians’ and sociologists’ views in 1874-2010 period how the historical relations between science and religion should be presented. The key theories have been discussed which are the milestones in this evolution: from 19th century Draper’s and White’s works which formed the so called conflict thesis to the present complexity thesis, which recognizes the religion as significant co-originator of modern science.